Perlindungan Hukum Terhadap Kebebasan Berserikat Bagi Pekerja di Indonesia dan Malaysia - Siti Nurjanah; Rina Kusniati (Fakultas Hukum, Universitas Internasional Batam, 2017)
Everyone, including the government of a country needs to be aware of the importance of human rights as one as the natural right. One of them is the freedom to associate, including the freedom to associate for the employees. The intention of the author in this thesis is to make a review about provision of legal protection for employees in the State of Indonesia and Malaysia, in terms of providing fulfillment to employee’s right, as one of human rights. The methodology by author in this research is used the normative legal research based on comparative law. The data in this research is used secondary data obtained from the study of literature (library research). After the required data has been collected, it will be processed and analyzed to find the object of legal issues. Furthermore, the authors will provide a conclusion and describe the conclusion descriptively. The result of this research indicates that the State of Indonesia and Malaysia already have provisions on freedom of association for employees. The difference between provisions of Indonesia State and Malaysia State is the Indonesian State has a firmer provision than the State of Malaysia, Indonesia also provide the better law protection for freedom of association for employees in the country.